Correction of Hunter syndrome in the MPSII mouse model by AAV2/8-mediated gene delivery - Monica Cardone; Vinicia Assunta Polito; Stefano Pepe; Linda Männ; Alessandra d’Azzo; Alberto Auricchio; Andrea Ballabio; Maria Pia Cosma (2006)
Mucopolysaccharidosis type II (MPSII; Hunter syndrome) is a lysosomal storage disorder caused by a deficiency in the enzyme iduronate 2-sulfatase (IDS). At present, the therapeutic approaches for MPSII are enzyme replacement therapy and bone marrow transplantation, although these therapies have some limitations. The availability of new AAV serotypes that display tissue-specific tropism and promote sustained expression of transgenes offers the possibility of AAV-mediated gene therapy for the systemic treatment of lysosomal diseases, including MPSII. We have characterized in detail the phenotype of IDS-deficient mice, a model of human MPSII. These mice display a progressive accumulation of glycosaminoglycans (GAGs) in many organs and excessive excretion of these compounds in their urine. Furthermore, they develop skeleton deformities, particularly of the craniofacial bones, and alopecia, they perform poorly in open-field tests and they have a severely compromised walking pattern. In addition, they present neuropathological defects. We have designed an efficient gene therapy approach for the treatment of these MPSII mice. AAV2/8TBG-IDS viral particles were administrated intravenously to adult MPSII mice. The plasma and tissue IDS activities were completely restored in all of the treated mice. This rescue of the enzymatic activity resulted in the full clearance of the accumulated GAGs in all of the tissues analyzed, the normalization of the GAG levels in the urine and the correction of the skeleton malformations. Overall, our findings suggest that this in vivo gene transfer approach has potential for the systemic treatment of patients with Hunter syndrome.